(x) = -2x - 7 y = f(x) = -2x -7 then solve for x: -2x = y + 7 x = (y+7)/(-2) = (-y-7)/2 rewrite in terms of x: f^(-1)(x) = (-x-7)/2 Compose the inverse f^(-1) with the function f. then input x. f^(-1) o f(x) = f^(-1)(-2x-7) = [-(-2x-7) - 7]/2 = [+2x + 7 - 7]/2 = 2x/2 = x for all values of x

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up